2017
DOI: 10.1080/17290376.2017.1394908
|View full text |Cite
|
Sign up to set email alerts
|

Problematizing official narratives of HIV and AIDS education in Scotland and Zimbabwe

Abstract: When human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) are framed within an intersectional approach, they have the potential to transform understandings of social justice within the curriculum and education policy and practice in general. Yet, this transformative potential is often hampered by official narratives that fail to position HIV and AIDS as an integral component of overlapping systems of oppression, domination and discrimination. This article explores how official HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These results replicate those found in a DCE conducted among ART patients who were lost to follow-up in Zambia, confirming that the attitude of HCWs was the most important factor in driving preferences for services [ 30 ]. Of concern, previous studies have found that HCWs retain negative attitudes toward people living with HIV, citing issues relating to inter alia , personal beliefs, fear of contagion, cultural differences, existing stigma around HIV and discrimination toward people living with HIV that is still pervasive in some communities [ 28 , 31 , 32 ]. Given the importance of this characteristic to patients, DART models must ensure they are staffed by HCWs who are respectful and understanding, in an effort to increase patient satisfaction and utilization.…”
Section: Discussionmentioning
confidence: 99%
“…These results replicate those found in a DCE conducted among ART patients who were lost to follow-up in Zambia, confirming that the attitude of HCWs was the most important factor in driving preferences for services [ 30 ]. Of concern, previous studies have found that HCWs retain negative attitudes toward people living with HIV, citing issues relating to inter alia , personal beliefs, fear of contagion, cultural differences, existing stigma around HIV and discrimination toward people living with HIV that is still pervasive in some communities [ 28 , 31 , 32 ]. Given the importance of this characteristic to patients, DART models must ensure they are staffed by HCWs who are respectful and understanding, in an effort to increase patient satisfaction and utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of viewing characteristics like gender expression or poverty in isolation, intersectional theory codified efforts to examine these individual axes of difference in tandem [6]. It also encouraged researchers to critically examine how systems of oppression interact at the societal, community, and individual levels [710].…”
Section: Introductionmentioning
confidence: 99%
“…The need to recognize an individual’s membership in multiple stigmatized groups has been a relatively recent consideration in the public health literature [1, 15, 16]. This acknowledgement is largely due to efforts to understand HIV-related stigma not only as a manifestation of fears related to the health condition itself, but also negative attitudes regarding behaviors and identities originally associated with HIV transmission (e.g., sexual practices or orientation, injection drug use, and sex work) [10, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, GBQMSM who seek testing face stigma related not only to a possible HIV diagnosis, but also to same-sex sexual behaviors [14]. Moreover, HIV-related stigma itself is intertwined with negative attitudes, often expressed interpersonally between people, towards samesex sexual practices and identities (e.g., [22]). Reflecting this intertwinement, a recent survey of Australian GBQMSM found that 70% reported experiencing interpersonal stigma due to perceived HIV risk despite the fact that only 5% actually reported being that they were PLWH [23].…”
Section: Introductionmentioning
confidence: 99%